Padlet: a tool for fostering collaborative learning and feedback literacy in dental education - Avita Rath (Frontiers in Medicine)
BackgroundWhile health professions education has embraced collaborative and co-creative learning approaches, the integration of digital technologies into feedback practices remains limited, especially in undergraduate dental education. This study investigated the impact of Padlet, a digital pinboard, on collaborative learning and feedback literacy among undergraduate dental students during a formative assessment activity guided by Nicol and MacFarlane's feedback principles.MethodsA convenience sample of 39 Year 3 dental students (25 women and 14 men, mean age = 22) enrolled in a Bachelor of Dental Surgery program at a private dental school in Malaysia participated in a week-long Padlet-based peer feedback activity focused on periodontics. Thematic analysis was conducted on student interactions and reflections collected from Padlet posts and individual student reflections.ResultsThe study yielded promising outcomes. Padlet's asynchronous and anonymous nature fostered in-depth discussions, broader participation, and constructive feedback. Students reported a boost in confidence, increased engagement, and a sense of camaraderie. Thematic analysis revealed the successful application of Nicol and MacFarlane's feedback principles, including clarifying expectations, promoting self-assessment, facilitating teacher–student dialogue, and encouraging reflection and action.ConclusionThe findings of this study suggest that Padlet, with its unique features, offers a valuable tool for educators seeking to foster collaborative learning and feedback literacy in dental education. Padlet's affordances can significantly enhance collaborative learning and feedback literacy, promoting a trusting environment for student-centered learning and self-regulation in dental education. The study's findings suggest that Padlet can foster cognitive flexibility, allowing students to consider multiple perspectives and adapt their thinking. The platform's asynchronous nature and anonymity feature appeared to contribute to a sense of community and psychological safety, fostering trust among students. The findings of this study have practical implications for educators seeking to implement effective feedback practices and leverage technology to create engaging learning experiences that foster trust, collaboration, and, ultimately, student success.